Evaluation of Surgical Management of Multinodular Goiter - Khallas, Dr. Zahdam Shabeeb; Jawad, Dr. Samer Shakir; Gubari Zukait, Dr. Mohanad (Journal of Science in Medicine and Life, 2024)
Background: Goiter is a worldwide problem, particularly predominant in areas with iodine deficiency?. It is still endemic in various parts of Iraq and endemic goiter most commonly found in the north and middle of Iraq and in the capital Baghdad3,4 Multinoduiar goiter is a relatively common condition with a marked female predominance. The etiology of this condition remains unclear but it is probably multifactorial : heredity, dyshormonogenesis, iodine deficiency, naturally occurring goiterogens and circulating thyroid growth factors are possible contributors. The thyroid gland is known to become more nodular with age. Aim: The aim of study is to evaluate the mode of presentation, the surgical management, the complications and the incidence of malignancy among a cohort of patients with multinoduler goiter. Patients and Methods:This is a prospective study carried on 195 patient diagnosed as multinodular goiter for surgery and admitted to. Hilla General Teaching Hospital/Babel Health Directorate, between the first of Jan. 2010 to the first of Jan. 2013. The patients were divided into six age groups. The majority of them were in the second and third age group i.e. (21-30) ,31-40) years respectively with female predominance in both (P.value 0.001). Results: Unsightly swelling in the neck was the most common presenting symptom (70% followed by toxic features (18%, obstructive features (8.5%) of patients. Most common indication of surgery was unsightly swelling of neck (65%), toxic changes (16.5%), pressure symptoms in (8.5%) • Subtotal thyroidectomy was the most common procedure (58%) followed by hemithyroidectomy (Right and Left followed by total and near total thyroidectomy Regarding postoperative complications were seroma (5%), superior Laryngeal nerve injury(5%) wound infection (1.5%), and, recurrent laryngeal nerve injury (1.5%) only. Malignancy was found in (6.5%) of patients. They were papillary carcinoma (53.8%) and follicular carcinoma (30.7%). Conclusions: Recurrent laryngeal nerve injury can be avoided without special dissection to identify the nerve and further studies should be conducted to prove this.